(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article deals with the question of the linguo-psychological basis of speech activity. The features of speech within the limits of various sciences - psychology, physiology, linguistics are also considered. The physiological mechanisms of speech, the mechanisms associated with the transition from the plan (program) to the grammatical (syntactic) structure of the sentence have been studied